Method for Improving Critical Strategic and Operational Success Factors in a Port System - Palominos-Villavicencio, F (Elsevier B.V., 2018)
This paper discusses the governance and its action over the port business where private companies and public organizations participate. The sources of strategic inefficiencies that affect competitiveness are identified in the context of political, technological, economic, and social aspects. Strategic inefficiencies, business and operational, that affect the decision-making process, are detected in port activity. These are related to port governance, loss of time, logistical costs and lack of human capital. Critical factors affected by inefficiencies in export/import logistics chains are also detected which, if overcome, may reduce their logistical costs and increase port competitiveness. The greatest inefficiencies found in the public components and the private companies are related to waiting time (lead time) and time delays caused by the actors in the port business. It is observed that all strategic interest groups are not involved in the system and a lack of synergy is also perceived at business and operational levels in both public organizations and private companies. Logistic costs related to transport, inventory, storage, together with administrative and supply costs are also considered. The trends of the indicators presented in the paper allow the monitoring of the factors of inefficiency detected in the port activity. © 2018 The Authors. Published by Elsevier B.V.